ANALISIS PENDAPATAN USAHATANI CENGKEH DI KECAMATAN GOLEWA SELATAN KABUPATEN NGADA - Veronika Kae; Wiendiyati Wiendiyati; Hans L. Telnoni (Buletin Ilmiah Impas, 2019)
ABSTRACT Research the income analysis of household clove farming inSouthGolewa Sub – district Ngada District was held in March 2018. This study aims to determine : 1) implementation of farming in the southern Golewa sub – district, 2) income level of clove farming housholds in the southern Golewa sub – district. The method used is the survey method, sampling is done in stages. The first stage was two villages that were deliberately carried out, the selected villages were Takatunga village and Sadha village. The second stage, determining the sample farmer conducted by disproposionate stratified random sampling based on plant age, 32 respondents were obtained, so that the Takatunga village was obtained by 16 respondents and Sadha village was obtained by 16 respondents. The results showed that: 1) farmers carried out clove farming on plantation land, with an average land ownership of 0,36 ha, in the range of 0,09 ha to 2 ha. Labor used when plants are still under 8 years old using family labor, whereas in plants over 8 years old use rental labor, especially in harvesting. 2) the cost structure incurred by farmers on clove farming includes investment costs and operational costs, the size of which is greatly influenced by the ownership of plants. Invesment costs in the reseach area amounted to Rp 157.344 per tree, while the operational costs were Rp 495.344 per tree. Clove farm income per tree in Takatunga village and Sadha village ranges from Rp 240.000 to Rp 7.262.800, while the income of clove farmers based on tree ownership ranges from Rp 720.000 to Rp 486.607.600. ABSTRAK Penelitian ini dilaksanakan pada bulan Maret 2018. Tujuan ini bertujuan untuk mengetahui : 1) Pelaksanaan usahatani di Kecamatan Golewa Selatan, 2) Tingkat pendapatan usahatani cengkeh pada rumah tangga di Kecamatan Golewa Selatan Kabupaten Ngada. Metode yang digunakan adalah metode survei, pengambilan sampel dilakukan secara bertahap. Tahap pertama adalah dua Desa yang dilakukan secara sengaja (purposive sampling), Desa yang dipilih adalah Desa Takatunga dan Desa Sadha. Tahap kedua, penentuan petani contoh yang dilakukan secara Dispropotionate Stratified Random Sampling berdasarkan umur tanaman, maka diperoleh 32 responden, sehingga Desa Takatunga diperoleh 16 responden dan Desa Sadha diperoleh 16 responden. Hasil penelitian menunjukan bahwa : 1) rata – rata kepemilikan lahan usahatani cngkeh 0,36 ha, pada kisaran 0,09 ha sampai dengan 2 ha, 2) Struktur biaya yang dikeluarkan petani pada usahatani cengkeh meliputi biaya investasi dan biaya operasional, yang besar kecilnya sangat dipengaruhi oleh kepemilikan tanaman. Biaya investasi cengkeh di daerah penilitian sebesar Rp 157.344 per pohon, sedangkan biaya operasional Rp 495.589 per pohon. 3) Pendapatan usahatani cengkeh per pohon di Desa Takatunga dan Desa Sadha berkisar Rp 240.000 sampai dengan Rp 7.262.800, sedangkan pendapatan petani cengkeh berdasarkan kepemilikan pohon berkisar Rp 720.000 sampai dengan Rp 486.607.600.